Performance of piezoelectric energy harvester with various ratio substrate and micro windmill - Adhes Gamayel; Ade Sunardi (Universitas Ahmad Dahlan, 2024)
One of the mechanical energy harvesters, piezoelectric energy harvesters (PEHs), produces electricity in response to an external load, which leads to stress and strain in the cantilever beam. The study focused on performance PEH due to collisions between micro windmill blades and PEH substrate. The substrate has dimensions of 10 cm × 6 cm × 1 mm in length, width, and thickness, respectively. Experimental setup was in wind tunnel with a cross-section of 250 mm × 250 mm and blower to generated wind flow inside the tunnel. The wind speeds were set up at 6, 7, and 8 m/s, and then three ratios, namely 1:1, 1:2, and 1:3, were analyzed in output voltage and the deflection. The performance of energy harvesting in a ratio of 1:1 and wind speed of 8 m/s produces a deflection of 2.05 cm, the highest voltage of 12.67 volts, and an effective voltage of 5.62 volts. It was found that ratio 1:1 has a greater mass weight and cross-section than others, leading to more curvature in the PEH beam when the collision occurs. Besides that, the high speed of the micro windmill rotation causes collisions between the blades and PEH to become more frequent.